Treasury Flows Overview - Cornelia Elena Tureac; Anca Gabriela Turtureanu (European Financial and Accounting Journal, 2009)
The balance sheet presents the liquidities balance and the liquidity equivalents of the company at the end of the period. By examining the balances referring to the two consecutive periods, it can be stated that if the liquidities and the liquidity equivalents have increased or have decreased during the period. But the balance does not indicate why these balances have varied during the exercise. The profit and loss balance presents the information related to incomes, expenses and the results due to the different activities – key-points regarding the sources and the use of the liquidities and the liquidity equivalents, but this financial situation does not explain why the respective elements have increased or decreased. Even further, not on fewer occasions behind some significant profits, the profit and loss balance can hide serious treasury problems of the company.
Keywords: M41; 650; Treasury Flows; Painting Flows; Balance Sheet; Liquidity